The effect of maternal age on stunting incidence (Analysis of 2018 Riskesdas Secondary Data) - Sulistyawati, Feni; Melinda, Ade; Ratnasari, Ririn (Alma Ata University Press, 2024)
Background: Stunting is a nutritional problem in children which is characterized by the child's height not meeting the age standards set by WHO. Indonesia is the country with the highest prevalence of stunting. Stunting has the impact of delays in various sectors, especially health, in the short term, namely increasing morbidity and mortality rates. Stunting is caused by household factors, one of which is maternal factors. One of the reasons children are stunted is the mother's age, which is still in the adolescent range. Teenage moms who become pregnant often lack the knowledge necessary to ensure their unborn kid has a healthy diet, which can lead to stunting in the infant.Objectives: This study aims to determine the effect of maternal age on the incidence of stunting in children aged 0-59 months based on 2018 Riskesdas data.Methods: This research is a quantitative study with an analytical cross-sectional design using secondary data analysis based on survey results from Riskesdas in 2018. Data collection was carried out in March 2018 by the Central Statistics Agency (BPS) with locations in all provinces in Indonesia consisting of 34 provinces. The sample used was adjusted to the inclusion criteria, namely 69,155 mothers and toddlers aged 0-59 months. Research analysis was carried out using SPSS in stages based on a description of the research results and frequency distribution by presenting tables on the variables studied and using bivariate analysis simple binary logistic regression with Crude OR results with a confidence level of 95%.Results: The results obtained in this study were that there was a significant influence between maternal age and the incidence of stunting with a p value = 0.003. As many as 17.7% of stunting incidents in toddlers were experienced by teenage mothers.Conclusions: There is an influence of maternal age on the incidence of stunting in toddlers. It is hoped that health institutions can increase awareness regarding early marriage which can cause stunting.